Correlation of numerical and experimental analysis for dynamic behaviour of a 3 blade propeller structure - Brapakaran, Paranitharan; Abdullah, N. A. Z.; M. Fouzi, S. M.; Sani, M. S.M. (Institute of Physics Publishing, 2019)
In pursuance of deciding the dependability of data gathered by testing a finite element modal in the software version, experimental data is frequently used for validation. On account of finite element analysis, it can sometimes be considered as inaccurate particularly when applied to the complex structure, for example, a propeller blade. This is because of challenges that may happen in the modelling of joints, boundary conditions, and damping of the structure. In this research, a procedure of correlation and validation of the model-based test plan with modal testing results was conducted. Modal properties (normal frequencies, mode shapes, and damping ratio) of a propeller blade structure were resolved by using both test experimental modal analysis (EMA) and finite element analysis (FEA). Correlation of both sets of data was performed for validation. It created the impression that there was a noticeable estimation of error between those two sets of data. Small discrepancies of percentage error of obtained natural frequency for FEA and EMA makes both of the methods can be applied to determine the dynamic characteristic of the propeller structure.